Pengaruh Kualitas Pelayanan Personel Pengamanan Bandar Udara Terhadap Kepuasan Penumpang di Bandar Udara Internasional Yogyakarta - Alvina Nurul Faoziah (Jurnal Multidisiplin Madani, 2022)
This study aims to measure how far the influence of the service quality of airport security personnel on passenger satisfaction at Yogyakarta International Airport. Excellent service quality greatly affects passenger satisfaction. The research method used is descriptive quantitative by using the technique of Probability Sampling with Simple Random Side. Data collection is done offline and online. The results of this study indicate that the simple linear regression test gets a constant value of 4,600 which is a consistent value of Passenger Satisfaction (Y). while the results of the t test (partial) get a significant value of 0.000 which means that the value is smaller than the value of = 0.05 with a regression coefficient of 0.699 (positive), with the output results listed, it can be stated that the Quality of Airport Security Personnel Service has an influence which is positive and significant to Passenger Satisfaction. This shows that the hypothesis Ha is accepted and H0 is rejected.